2015
DOI: 10.1093/fampra/cmv065
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic labelling influences self-rated health. A prospective cohort study: the HUNT Study, Norway

Abstract: Background.Studies have shown an independent association between poor self-rated health (SRH) and increased mortality. Few studies, however, have investigated any possible impact on SRH of diagnostic labelling.Objective.To test whether SRH differed in persons with known and unknown hypothyroidism, diabetes mellitus (DM) or hypertension, opposed to persons without these conditions, after 11-year follow-up.Methods.Prospective population-based cohort study in North-Trøndelag County, Norway, HUNT2 (1995–97) to HUN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 35 publications
3
15
2
1
Order By: Relevance
“…In contrast to the findings of Jørgensen et al [29], those with undiagnosed diabetes reported significantly poorer health status than those with known diabetes. The former group also reported poorer overall health and psychological well-being compared with the other diabetes categories; however, this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 92%
“…In contrast to the findings of Jørgensen et al [29], those with undiagnosed diabetes reported significantly poorer health status than those with known diabetes. The former group also reported poorer overall health and psychological well-being compared with the other diabetes categories; however, this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 92%
“…To underscore, these people considered themselves well at baseline, but upon entering the study, they were all regarded as in suboptimal health. This entails a change in identity, and may result in pathologization and worry 20,21 .…”
mentioning
confidence: 99%
“…It may also stifle important debates about what physicians and scientists are actually doing when, for example, they label someone as ‘at risk’ or as afflicted by ‘bipolar’, ‘PTSD’ or ‘chronic Lyme’. Moreover, by selecting a reference of health and making any deviation of functioning from that reference the responsibility of the individual or a public health system, one effectively labels an unknown segment of the population as deviants with respect to optimal health, thereby potentially also inflicting iatrogenic harm such as anxiety or altered self-image [ 47 ]. It is far from obvious that this important definitional work can be left to scientists at the ISB or other abstract agents ‘skilled in the art’.…”
Section: Discussionmentioning
confidence: 99%